Assessing motivational interviewing via co-active life coaching on selected smoking cessation outcomes. (April 2015) - Mantler, Tara; Irwin, Jennifer D.; Morrow, Don; Hall, Craig; Mandich, Angela
Abstract The objective of this study was to assess the impact of Motivational Interviewing (MI)-via-Co-Active Life Coaching (CALC) on: smoking behaviours, personal competency as well as changes in perceptions of identity, smoking, quitting and the intervention itself among young adults (aged 19–25 years) in Canada. A mixed methods intent-to-treat approach was taken; the impact of 8–10 MI-via-CALC sessions on smoking behaviour and personal competency of 40 young adult smokers was examined through both questionnaires and individual interviews over 1 year. The immediate-intervention group received MI-via-CALC starting right after enrolment, whereas the waitlist-intervention group was placed on a waitlist for 3 months and then received the intervention. The immediate-intervention group decreased significantly from baseline to post-intervention in smoking behaviours, including the number of cigarettes smoked per day and cigarette dependency; and increased significantly in personal competency, including self-esteem and self-efficacy compared with the waitlist-intervention group. Moreover, 27.5% of participants after receiving the intervention were smoke-free at 12-month post-intervention follow-up. Additionally, qualitative themes pertaining to perceptions of identity, smoking, quitting and the intervention and their changes over time were described and were consistent with quantitative findings. Together, the high cessation rate for the entire study as well as the significant decreases in smoking behaviours and increases in personal competency of the intervention group compared with the waitlist group underscore the impact on behaviour change. MI-via-CALC offers a theoretically grounded, practical and efficacious cessation strategy for young adult smokers.